Contemporary Challenges in Postnatal Care (IntechOpen, 2024)
This book is a unique collaboration of international healthcare providers discussing and addressing contemporary issues in postnatal care. Its discussion spans low-, middle-, and high-income countries. It addresses barriers and challenges to providing optimal postnatal care, suggesting interventions, support strategies, and recommendations. These include empowering women economically and socially, providing education, training healthcare professionals, and establishing healthcare infrastructure to improve access and utilization of postnatal care for families worldwide.